Ochratoxigenic fungi in post-fermented tea and inhibitory activities of Bacillus spp. from post-fermented tea on ochratoxigenic fungi. (August 2021) - Zhao, Zhenjun; Lou, Yougen; Shui, Yucheng; Zhang, Jian; Hu, Xianchun; Zhang, Lingling; Li, Mengqiao; Wu, Huawei; Li, Xinghui
Abstract: The contamination of ochratoxigenic fungi in the process of pile-fermentation of post-fermented tea is objective, but the fact that ochratoxigenic fungi have almost no risk to the safe drinking of post-fermented tea products has been widely concerned. This study aims to identify the diversity of ochratoxigenic fungi in post-fermented tea and to reveal the inhibitory effect of Bacillus strains isolated from post-fermented tea on ochratoxigenic fungi. Results showed: 8.33% of A. niger strains, 30% of A. tubingensis strains, 100% of A. carbonarius strains, A. nidulans strains, P. verrucosum strains and A. ochraceus strains isolated from post-fermented tea have the ability to produce ochratoxin A (OTA), and there are significant differences in the OTA production ability between different strains. The six different species of Bacillus isolated from post-fermented tea coexisted with ochratoxigenic fungi in liquid media can not only inhibit the growth of ochratoxigenic fungi, but also inhibit the production of OTA. Bacillus strains cocultured with ochratoxigenic fungi on the tea matrix also have significant effects on the growth of OTA-producing fungi and the effects of inhibiting fungi are influenced by the order of inoculation, culture time and the difference of fungal species. Bacillus crude antifungal extracts have inhibitory effects on the growth of OTA-producing fungi and anti-fungal substances can be roughly divided into two categories: peptides with molecular weight ≤10 kDa, and anti-fungal proteins with molecular weight >10 kDa according to their molecular weight. The research results have important guiding value for the correct understanding of the hazards of fungal contamination in post-fermented tea and searching for new technologies of producing post-fermented tea aimed at reducing the safety risks of OTA. Highlights: Ochratoxigenic fungi from post-fermented tea were diverse. Bacillus strains from post-fermented tea inhibit the growth of ochratoxigenic fungi. Bioactive substances produced by Bacillus contain peptides≤10 kDa and proteins>10 kDa. The research revealed the complexity of fungal contamination in post-fermented tea. Evaluated efficacy of antagonistic strains against ochratoxigenic fungi in tea.